Accidents among postmen using motorbikes for mail deliveries in Tuscany in the period 2007-2009 - Chellini, Elisabetta; Cortini, Barbara; Mameli, Marina; Abbarchi, Mauro; Dei, Simona; Rossi, Oriana; Zallocco, Alfredo (La Medicina del Lavoro, 2014)
Background: Health risks for postmen using motorbikes for mail delivery may be influenced by stability, weight and ease of handling of the vehicle, traffic and slippery or irregular road surface. Objectives: To describe accidents that occurred among postmen in Tuscany and evaluate how many of these would have been prevented using the UNI EN 13595/2004 safety jacket. Methods: Record linkage of data obtained from the employer – the main mail delivery company in Italy - and from the Italian Workers Compensation Authority on accidents that occurred in postmen in  Tuscany who used motorbikes for deliveries during the period 2007-2009. Accident rates (with CI95%) by age, sex, year and province were calculated; the differences were evaluated using χ2 test. Results: 1,342 accidents requiring at least 3 days’ sick absence were recorded in postmen in Tuscany in the period 2007-2009, with an increasing trend in young men. The average accident rate was 17.6 per 100 workers, with 42,419 sick absence days. The female rate was higher compared to men (19.4%, CI95% 18.03-20.79 in women vs 15.5%, CI95%: 14.15-16.89 in men). 68% of accidents occurred driving a motorbike. The index of severity was 6.79, which was higher than that calculated by INAIL for the whole Tuscan transport and communication work sector (5.31). 309 accidents (11,021 sick absence days) could have been mitigated or avoided using UNI EN 13595/2004 safety jackets (47% spinal, 30% shoulder, 23% elbow, arm and forearm). Conclusions: The frequency of accidents in postmen using motorbikes is extremely high. Several serious accidents could have been prevented using the UNI EN 13595/2004 safety jackets, suggesting the need to make their use  obligatory  by these workers.